Cognitive Testing to Identify Children With ADHD Who Do and Do Not Respond to Methylphenidate. (December 2017) - Elliott, Glen R.; Blasey, Christine; Rekshan, William; Rush, A. John; Palmer, Donna M.; Clarke, Simon; Kohn, Michael; Kaplan, Craig; Gordon, Evian
Objective: To explore the utility of cognitive measures for predicting response of children and adolescents to methylphenidate (MPH).Method: Participants from the International Study to Predict Optimized Treatment–in ADHD (iSPOT-A) completed a cognitive test battery prior to receiving 6 weeks of MPH. The responder criterion was a 25% reduction in ADHD-Rating Scale-IV scores. Receiver Operator Characteristics (ROC) classified non-responders from responders with maximal sensitivity and specificity.Results: Overall, 62% of participants responded to MPH. Response rates for ROC-identified groups ranged from 18% to 85%. Non-responders showed compromised cognition related to switching of attention, sustained attention, planning, and impulsivity. One group of responders were 10 years of age or older and had impaired switching of attention and impulsivity; a second group had enhanced switching of attention, normal or higher Continuous Performance Task (CPT) scores, and above average scores on digit span.Conclusion : Cognitive tests may provide a simple, low-cost tool for treatment planning for children and adolescents with ADHD.